A long-term macroecological analysis of the recovery of a waterbird metacommunity after site protection. - Janina Pagel (Public Library of Science (PLoS), 2014)
We used the so called "land-bridge island" or "nested-subsets" theory to test the resilience of a highly fragmented and perturbated waterbird metacommunity, after legal protection of 18 wetlands in the western Mediterranean. Sites were monitored during 28 years and two seasons per year. The metacommunity was composed by 44 species during breeding and 67 species during wintering, including shorebirds, ducks, herons, gulls and divers (Podicipedidae). We identified a strong nested pattern. Consistent with the fact that the study system was to a large extent a spatial biogeographical continuous for thousands of years, fragmented only during the last centuries due to human activities. Non-random selective extinction was the most likely historical process creating the nested pattern, operated by the differential carrying capacity (surface-area) of the remaining sites. We also found a positive temporal trend in nestedness and a decreasing trend in species turnover among sites (β-diversity), indicating that sites are increasingly more alike to each other (i.e. increased biotic homogenization). This decreasing trend in β-diversity was explained by an increasing trend in local (α) diversity by range expansion of half the study species. Regional (γ) diversity also increased over time, indicating that colonization from outside the study system also occurred. Overall our results suggest that the study metacommunity is recovering from historical anthropogenic perturbations, showing a high long-term resilience, as expected for highly vagile waterbirds. However, not all waterbird groups contributed equally to the recovery, with most breeding shorebird species and most wintering duck species showing no geographical expansion.